Vertical and inverted vertical learning transmission effect with some educational tutorials to learn the skills of the forehand and backhand tennis - Jabbar Abbas, Ammar (International Journal of Psychosocial Rehabilitation, 2020)
require proces learning Use better Software educational followed and implement them shape the correct to guarantee Access to me Target From the operation educational the lowest an effort and faster time, and became Game tennis from Materials the basic that Studied in faculties Education So must We finding better roads and educational aids that Aims to me hurry up From proces learning and access to me higher Degree From mastering skills sports, and what that education at university system seasons And it depends on me Number hours van there time specific to reach to me Degree perfection in skill or Effectiveness educated or get over it From Without mastering, so Complete Then moving in to me skill the other And that to have Number a certain From skills course learn it During Period temporal specified for every Season, and what that transition Effect learning one the conditions the basic in the operation educational, From over here Originated Problem shorter time to learn, Where no Can teacher Stop or addition Lots From lessons extra And that to narrow the time, Therefore It was must From Use Techniques educational acceleration From proces learning From During Help learner on me link his thoughts his thoughts and his experiences Previous in the present laxative and speeding for operation learning, like that Use means educational for his condition Play Real which help on me, a knowledge learner all variables the performance that faces the learner during The competition, and given me research that headed to my area ranking start learn skills the basic tennis From easy to Difficult and vice versa And by on me Use educational aids, i want researcher start with this step to study transition Effect learning vertical and vertical inverted using some means educational to learn Skill forehand and the background tennis